Ethics And Social Responsibility as Performance Indicators of The Accounting Professional in The Ecuadorian Environment - Castillo, Norma del Rocío Toledo; Torres, Patricia Maria Salazar; Garcia, Javier Ignacio Briones (International Journal of Membrane Science and Technology, 2023)
The work performance of accounting professionals, under traditional paradigms, was measured by their ability to analyze financial statements and determine the economic performance indicators of organizations, however today, in addition to technical aspects, they must possess related competencies. to social responsibility and ethics, in such a way that their work has a positive impact on society by carrying out work with transparency that allows keeping clear accounts. With the objective of evaluating the importance of the qualities social responsibility and ethics in the evaluation of the performance of the accounting professional in the Ecuadorian environment, a systematic review was carried out, through the bibliographic consultation of 200 articles in the database of indexed journals in Scopus, Latindex, Scielo, and Google Scholar, selecting the articles that describe the importance of considering social relevance and respect for ethical standards and values, within the professional actions of Ecuadorian accountants. As a result of the review, 36 articles were selected, which highlight that in Ecuador, despite the existence of a code of ethics for the profession, the paradigm shifts that tend to measure the efficiency of companies due to their relationship with society, respect for environment and transparent management of accounts, in addition to the well-known financial indicators, forces a change in the profile of the Ecuadorian accounting professional and with it the training plans of university institutions, this new vision of the accounting practice leads to the conclusion that an exercise of greater transparency will be observed during the financial analysis of companies, especially those linked to the public sector, which are characterized by high levels of corruption.